Exploring English Learning Experiences among Health Administration Students: Challenges, Role-Play, and Digital ReadinessExploring English Learning Experiences among Health Administration Students: Challenges, Role-Play, and Digital Readines - Ariani Rosadi; Lubis Hermanto; Muhammad Wardhani; Hanafi Hanafi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
a